Evaluation of alveolar bone thickness at anterior areas of the jaws in subjects with class I and class III malocclusions - Mostafa Shahabi; Farzaneh Ahrari; Hossein Hosseini Zarch; Moha Alavi (Mashhad University of Medical Sciences, 2023)
Introduction: Considering the morphology of alveolar bone is of great importance in orthodontic treatment planning. This study aimed to investigate the thickness of the anterior alveolar bone of the jaws in subjects with class I and class III malocclusions. Materials & Methods: This cross-sectional study evaluated 50 CBCT images of the upper jaw and 20 CBCT images of the lower jaw obtained from the archive of a Radiology Center. The selected patients had equal numbers of class I or class III malocclusions. The thickness of the alveolar bone was measured in the anterior parts of the maxilla and mandible at three areas including the apex, middle root and alveolar crest at both buccal and lingual sides. To assess data reliability, 20% of images were randomly selected and the measurements were repeated 10 days later. Independent sample t-test and chi-square test were used for statistical analysis.Results: There was no significant difference in the mean age (P=0.448) and gender (P=1.00) of the patients between the two groups. In the upper jaw, the mean alveolar bone thickness in class III patients was significantly lower at the buccal crest (P=0.015) and palatal apex (P<0.001) areas, and significantly greater at the buccal apex area (P<0.001), as compared to class I patients. In the lower jaw, bone thickness at the lingual side of the middle (P=0.024) and apical (P=0.045) root areas was significantly lower and at the bucco-apical region was significantly greater in class III than class I patients (P=0.049). There was no significant difference between the two groups concerning bone thickness at other regions of the upper and lower jaws (P>0.05) Conclusion: It is necessary to pay more attention to alveolar bone thickness at the buccal crest of the maxilla and lingual region of the mandible in class III patients undergoing orthodontic treatment.